2018
DOI: 10.1039/c8nj03165g
|View full text |Cite
|
Sign up to set email alerts
|

A multi-analyte responsive chemosensor vanilinyl Schiff base: fluorogenic sensing of Zn(ii), Cd(ii) and I

Abstract: A single fluorescence probe recognizes multiple ions and grabs the great attention of scientists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…The average lifetime of Zn‐SAP (3.67 ns) complex is increased by 60 times of free probe (t av , 0.06 ns) (Figure ). The metal‐ligand orbital mixing of delocalized 3d π orbital of Zn 2+ with π* of H 2 ‐SAP may be the reason for the longer lifetime of the excited state …”
Section: Resultsmentioning
confidence: 99%
“…The average lifetime of Zn‐SAP (3.67 ns) complex is increased by 60 times of free probe (t av , 0.06 ns) (Figure ). The metal‐ligand orbital mixing of delocalized 3d π orbital of Zn 2+ with π* of H 2 ‐SAP may be the reason for the longer lifetime of the excited state …”
Section: Resultsmentioning
confidence: 99%
“…As consequence, its contamination in food and environment is drastically increasing. [5] Exposure to cadmium may occur via inhalation or ingestion and it is estimated that 98 % of cadmium was ingested from terrestrial foods while 2.0 % from water and aquatic foods. [6] Cadmium is categorized by IARC as Group 1 -carcinogenic to humans-due to the reported influences such as DNA-repairing inhibition, epigenetic alterations, chromosomal damage, and genomic instability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these properties, the demand and consumption of this metal in agricultural and industrial areas is considerable and increases day by day. As consequence, its contamination in food and environment is drastically increasing [5] . Exposure to cadmium may occur via inhalation or ingestion and it is estimated that 98 % of cadmium was ingested from terrestrial foods while 2.0 % from water and aquatic foods [6] .…”
Section: Introductionmentioning
confidence: 99%
“…al reported methoxy substitution in difluoroboron benzoylacetonate complexes exhibiting color‐tunable phosphorescence and our research group also previously repoted the effect of ‐OMe substituent on salicylaldehyde based Schiff base to influence the Zn 2+ ion sensitivity. Again our research group already reported a Schiff base molecule which exhibited fluorescence sensitivity enhancement towards Zn 2+ , Cd 2+ and I − . In the present work, only the position of methoxy (‐OMe) group is differ from the previously reported molecule and a new vanillinyl‐hydrazone Schiff base, 2,6‐Bis‐[(2‐hydroxy‐3‐methoxy‐benzylidene)‐hydrazonomethyl]‐4‐methyl‐phenol (PHV) is synthesized which shows the minor change tunes the fluorescence sensitivity from Zn 2+ , Cd 2+ and I − to Zn 2+ , Cd 2+ , Mg 2+ and I − .…”
Section: Introductionmentioning
confidence: 99%
“…Again our research group already reported a Schiff base molecule which exhibited fluorescence sensitivity enhancement towards Zn 2+ , Cd 2+ and I − . In the present work, only the position of methoxy (‐OMe) group is differ from the previously reported molecule and a new vanillinyl‐hydrazone Schiff base, 2,6‐Bis‐[(2‐hydroxy‐3‐methoxy‐benzylidene)‐hydrazonomethyl]‐4‐methyl‐phenol (PHV) is synthesized which shows the minor change tunes the fluorescence sensitivity from Zn 2+ , Cd 2+ and I − to Zn 2+ , Cd 2+ , Mg 2+ and I − . On the other hand, S. Nandi et.…”
Section: Introductionmentioning
confidence: 99%